Toward a better understanding on the role of unsteadiness in swimming propulsion by means of PIV - Matsuuchi, K. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
The highly efficient locomotion of birds, insects and fish is based on unsteady dynamics. The centered mechanism in the locomotion is related with unsteady behaviour of vortices such as the formation in boundary layers and the shedding from it. Attention to the relation between an object and vortex movement was first noticed in the aeronautical field. The problem of a thin airfoil performing small lateral oscillations in a uniform stream of incompressible fluid, received interest for many years, at the heart of all flutter prediction. Much research within the limitation of the linear perturbation theory was published in early times. Welldocumented summaries, including Wagner`s work (1925) can be seen in Bisplinghoff (1955). While much attention was given to the lift sustaining insect and bird flights against their weight, relatively little interest have been given to the unsteady mechanism in swimming propulsion. In Colwin`s book (2002), we can find many detailed sketches of vortices generated in many stroke patterns. The only tool for analysing unsteady flow is the particle image velocimetry (shortly PIV). Even with the use of this sophisticated means, it is difficult to measure a whole flow field directly around human hand and foot. However, a great success was attained in the field of insect and fish locomotion. We mention about the principle of the PIV and its application to swimmers and then several flow fields generated by a motion such as a stroke of front crawl (Matsuuchi et al. 2009), mono-fin, and sculling motion of hand are visualized. Velocity and vorticity fields are especially important to understand the unsteady force generation. How unsteady flow is generated by the motion of hand and foot is discussed. Furthermore, direct measurement of unsteady force acting on a robot arm is made and is also compared with the unsteady properties of flow field obtained by PIV. REFERENCES: 1. Bisplinghoff R L, Ashley H, Halfman RL (1955). Aeroelasticity, Chap. 5, Addison-Wesley Pub. 2. Colwin CM (2002). Breakthrough Swimming, Chap.5, Human Kinetics. 3. Matsuuchi K, Miwa T, Nomura T, Sakakibara J, H. Shintani H, Ungerechts BE (2009). Unsteady flow field around a human hand and propulsive force in swimming, Journal of Biomechanics vol.42-1, pp.42-47.